Heart rate responses during small sided games and official match-play in soccer - Asci, A. (Sports, 2016)
Small sided games (SSGs) are a match specific type of training. In addition, there is an insufficient number of studies that compare heart rate (HR) responses of SSGs and official match-play (OM). The purpose of this study was to investigate the heart rate responses during SSGs and OM in young soccer players. Twenty-two male soccer players (mean ± SD; age 17.4 ± 0.9 years, height 174.9 ± 6.6 cm, body weight 67.7 ± 8.1 kg) volunteered to participate in this study. The first session included anthropometric measurements and a maximum running test (RT). Following the RT session, all players participated in five different randomly ordered SSG sessions (3-, 4-, 5-, 7- and 9-a-side with goalkeepers). OMs were also monitored in the fourth week of the study. A one-way multivariate repeated-measures analysis of variance (MANOVA) was then conducted to evaluate the differences between the SSGs and OM. The results showed that 3-a-side elicited significantly higher HR and %HRmax than other SSGs and OM, whereas 9-a-side resulted in significantly lower HR and %HRmax compared to other SSG formats and OM (p < 0.05). In conclusion, 3-a-side, 4-a-side and 5-a-side SSG formats provide players with the opportunity to spend sufficient proportion of time spent in high intensity zones that are specific to match demands.